Chế tạo vật liệu hấp thụ dầu trên cơ sở styren và lauryl metacrylat bằng phương pháp huyền phù - Dũng, Nguyễn Tiến; Công, Trịnh Đức; Khôi, Nguyễn Văn; Trịnh, Nguyễn Hữu (Vietnam Journal of Chemistry, 2014)
The oil absorption materials were prepared by the suspension copoly-merization of styrene(St), lauryl methacrylate(LMA) and divinylbenzene (DVB) as crosslinker. Some effect factors on the absorbency such as: monomer ratio, initiator concentration and crosslinker concentration were studied. The optimal conditions were as following: ratio of styrene/lauryl methacrylate 6/4 (w/w), 1.2 wt% BPO, 0.3 wt% DVB, temperature 90oC and time 4h. The oil absorbency of materials in different solvents was also investigated.